Platform Guru Pembelajar Dalam Kemandirian Belajar Siswa - Sekarrini, Nastiti Zahra; Supriatna, Nana; Ma'mur, Tarunasena (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Research on the Teacher Learner platform in independent learning is based on the findings of researchers at research locations which shows the use of learning platforms in learning history, this learning platform is used by students to learn independently. The learning teacher platform created and used by one of the history subject teachers at SMA IT Pesantren Nururrahman, the teacher created and operated this platform with the aim of being a learning tool for students in the school environment and in the home envirinment. This study will describe how students learning independence using the learning teacher platform. The learning teacher platform is one of the media that can be used by students to learn independently with learning material that have been provided by, so that the learning teacher platform can support the growth of students learning indeoendence.